E agora José e Maria? o encontro com a maioridade após uma vida em acolhimento institucional: aproximações Brasil e Portugal - Goes, Alberta Emília Dolores de (2019)
The institutionalization of children and adolescents followed the project of Portuguese domination of the original peoples, since the time of the Brazilian colonization. "Curumins", "negrinhos/as", "pivetes", "piás", "trombadinhas", street boys, kids, minors, children and adolescents, among others, were the forms of treatment that showed the way of seeing and being of this "unprotected" population in different historical moments in which institutionalization occurred. Following this direction, even with the changed time and sociopolitical context, the same logic still accompanies them. With all the humanitarian advances and milestones that support the guaranteeing system of rights of children and adolescents, it is not unusual, even today, the long-term institutionalization and, in some cases, throughout the whole childhood and adolescence. The present research was based upon the professional work as a social judicial worker, in the area of childhood and youth - from a disturbing and provocative daily life, with the indignation as main trigger. Thus, the objective of this study is to understand the trajectory of institutionalized children and adolescents in Brazil and Portugal, under protective measures of institutional care (in which they were delivered by their families or withdrawn from the family context, by right violations denouncements, among others) and which, guarded by the State and under the responsibility of Justice, were not reunited with their birth/extended families, nor were located applicants for their adoption, remaining institutionalized for a long time and / or until they completed the civil majority - and how they were organized after their deinstitutionalization. The research, with qualitative approach, was developed from the oral history of life perspective, having as subjects twelve young people and adults Brazilian and Portuguese. The voices of those Who went through the institutional shelter life and for a long time are the focus of this study and forms a mosaic of meanings, impressions and propositions, that allow to review this social space. Nowadays, the main link between Brazil and Portugal is the International Convention on the Children Rights (1989), an important legal framework that supports childrenrs rights. In these countries, institutional shelter care still proves to be an important protective measure for situations of lack of protection. However, it is observed that it cannot remain as its main answer, even for social inequities. The long stay in care services is a reality for the studied countries, and it can cause serious damages, such as: social and familiar uprooting; hopelessness; lack of references to life; production of stigmas; difficulties in interpersonal relationships; psychic illness; among others. Institutional shelter care must always aim to unsheltering. Thus, all the work to be developed should consider the Child and the adolescent (as part of his family of origin) as subject and not object of this experience. It is along this trajectory that these citizens-subjects and their protagonism are strengthened. The transition out of the care institution must be prepared in a continuous process, and the age limit cannot constitute a game-over used as a form of disengagement and de-protection of those involved. In Brazil and Portugal, it is still necessary to implement preventive / protective measures (which necessarily include the birth families of children and adolescents), alternatives to the sheltering care, as well as observing that the process of unsheltering lacks continuous preparation and subsequent mandatory follow-up, so that any problems for the previously sheltered can be remedied. This protective measure still encounters challenges to be faced by the authorities, the professionals and through public policies - with the necessary financing - that promote greater social equity, not the opposite